Extended spectrum ß-lactamase- and constitutively AmpC-producing Enterobacteriaceae on fresh produce and in the agricultural environment - Blaak, Hetty; van Hoek, Angela H.A.M.; Veenman, Christiaan; Docters van Leeuwen, Arieke E.; Lynch, Gretta; van Overbeek, Wendy M.; de Roda Husman, Ana Maria (International journal of food microbiology, 2014)
The attribution of fresh produce to the overall community-associated exposure of humans to ESBL- or AmpC-producing bacteria is currently unknown. To address this issue, the prevalence of ESBL- and AmpC-producing Enterobacteriaceae on fresh produce produced in the Netherlands was determined. Seven vegetable types that are consumed raw were selected: blanched celery, bunched carrots, chicory, endive, iceberg lettuce, mushrooms, and radish. The vegetables were mostly obtained from supermarkets. To determine whether the agricultural environment is the source of ESBL-producing Enterobacteriaceae on fresh produce, iceberg lettuce was also obtained directly from three farms, in conjunction with soil and irrigation water. ESBL-producing Enterobacteriaceae isolated from vegetables and environment were all environmental species: Rahnella aquatilis (n=119), Serratia fonticola (n=45) and Pantoea agglomerans (n=1). ESBL genes of R. aquatilis and S. fonticola were identified as blaRAHN-1 and blaRAHN-2 and blaFONA-1, blaFONA-2, blaFONA-3/6 and blaFONA-5, respectively. For R. aquatilis and S. fonticola, different prevalence numbers were observed using different isolation methods, which could at least partially be explained by an inverse correlation between the level of cefotaxime resistance of these species and incubation temperature. R. aquatilis was isolated from 0 to 46% of soil samples and 11 to 83% of vegetable samples, and S. fonticola from 2 to 60% of soil samples and 0 to 1.3% of vegetable samples. Third generation cephalosporin-resistant faecal Enterobacteriaceae were isolated from 2.7%, 1.3% and 1.1% of supermarket vegetables, iceberg lettuce from farms, and agricultural soil respectively. Faecal Enterobacteriaceae were all identified as Citrobacter and Enterobacter species and, with the exception of one Citrobacter koseri strain, all had phenotypes indicative of constitutive AmpC production. Comparison of fresh produce and its agricultural environment indicates that the Enterobacteriaceae population on fresh produce reflects that of the soil it is grown in. Public health risks associated with exposure to ESBL- and AmpC-producing bacteria through consumption of uncooked fresh produce are diverse. They range from occasional ingestion of 3GC-resistant opportunistic pathogens which may result in difficult-to-treat infections, to frequent ingestion of relatively harmless ESBL-producing environmental bacteria that may therewith constitute a continuously replenished intestinal reservoir facilitating dissemination of ESBL genes to (opportunistic) pathogens. •3GC-resistant Enterobacteriaceae were present on raw consumed fresh produce.•Detected were ESBL-producing environmental and AmpC-producing faecal bacteria.•ESBL genes identified were blaRAHN-1, blaFONA-1, blaFONA-2, blaFONA-3/6 and blaFONA-5.•3GC-resistant species on fresh produce reflected those in the farming environment.